Fractionation of nitrogen isotopes during amino acid metabolism in heterotrophic and chemolithoautotrophic microbes across Eukarya, Bacteria, and Archaea: Effects of nitrogen sources and metabolic pathways. (September 2017) - Yamaguchi, Yasuhiko T.; Chikaraishi, Yoshito; Takano, Yoshinori; Ogawa, Nanako O.; Imachi, Hiroyuki; Yokoyama, Yusuke; Ohkouchi, Naohiko
Highlights: Pure culture experiments for δ 15 NAA values in five chemotrophic microbes. First published data for δ 15 NAA in chemolithoautotrophic microbes and Archaea. Algae- or animal-like δ 15 NAA fractionation in microbes under different N sources. Specific metabolic pathways responsible for the δ 15 NAA fractionation. Abstract: The nitrogen isotopic composition of amino acids (δ 15 NAA ) is a promising tool for estimating the trophic position and nitrogen sources of organisms in grazing food webs. The utility of δ 15 NAA analysis of microbial processes in the biogeochemistry remains uncertain, because information about the δ 15 NAA values of chemotrophic microbes are still limited. In this study, we report the δ 15 NAA values in five cultured heterotrophic or chemolithoautotrophic microbes (one fungus, one bacterium, and three archaea) with controlled nitrogen sources in synthetic media. When the microbes were grown on ammonium, the apparent nitrogen isotopic fractionation of amino acids relative to glutamic acid in the microbes (e.g., −3.0 ± 1.0‰ for phenylalanine) was similar to those in algae. When the microbes were grown on a free amino acid mixture, the δ 15 N offsets of amino acids in the microbial cells relative to the amino acids in the culture media (e.g., +8.2 ± 0.8‰ for glutamic acid and +0.1 ± 0.2‰ for phenylalanine) were close to the standard isotopic fractionation between animals and their diets. These results suggest that the δ 15 NAA pattern can be used to distinguish two end-member metabolic modes in microbes (i.e., de novo synthesis of amino acids from inorganic nitrogen vs. assimilation of amino acids from environments). We also discussed the effects of metabolic pathways on the δ 15 NAA values and their fractionation with respect to the diversity of amino acid metabolism in microbes. These findings will form an important baseline for interpreting the δ 15 NAA values of organisms and detritus in natural environments.